(untitled) (Tanzania Medical Journal, 2022)
Background Infective keratitis is a commonly encountered ocular emergency and it is a major cause of corneal related blindness. The etiology and predisposing factors tend to vary with time and by geographic locations. Methods A hospital based cross sectional study was conducted at Muhimbili National Hospital (MNH) & Comprehensive Community Based Rehabilitation in Tanzania (CCBRT) hospitals among adult patients with infective keratitis from July to December 2020. Consecutive sampling was used to recruit 58 participants. A structured questionnaire was used to capture the demographics and predisposing factors for infective keratitis of the participant, and cornea-scrapping specimens were taken for microbiology laboratory tests. Data was analyzed using SPSS version 23. Results This study involved 58 participants who were attended and diagnosed to have infective keratitis at MNH and CCBRT during the study period. Majority (65.5%) of them were males. The median age of the participants was 36.30 years with a range of 18 years to 80 years. More than half (56.9%) of the participants presented to these tertiary eye hospitals late with blind eyes having visual acuities of less than 1.301 log MAR. Microbial etiology for infective keratitis in this study was bacteria in 84.5% of the participants. There was no single fungal isolate in both KOH mount and culture growth. The commonest bacteria isolate was Staphylococcus aureus in 36.1% of the participants. The leading predisposing factor for infective keratitis was a history of topical steroid use in 41.4% of the participants. Conclusion and Recommendations Microbial etiology for infective keratitis in Dar-es-Salaam is mostly bacterial and the leading predisposing factor for infective keratitis is topical steroid use. Therefore, initiatives should be taken to control irrational corticosteroid use to the eyes.